The Effect of Resveratrol on Mitochondrial Function in Myoblasts of Patients with the Common m.3243A>G Mutation - Motlagh Scholle, Leila (Biomolecules, 2020)
Mitochondrial function is essential for ATP-supply, especially in response to different cellular stressors. Increased mitochondrial biogenesis resulting from caloric restriction (CR) has been reported. Resveratrol (RSV) is believed to mimic the physiological effects of CR mainly via a sirtuin (SIRT) 1-dependent pathway. The effect of RSV on the physiological function of mitochondrial respiratory complexes was evaluated using a Seahorse XF96. Myoblasts of five patients harboring the m.3243A>G mutation and five controls were analyzed. The relative expression of several genes involved in mitochondrial biogenesis was evaluated for a better understanding of the coherent mechanisms. Additionally, media-dependent effects of nutritional compounds and hormonal restrictions (R) on myoblasts from patients and controls in the presence or absence of RSV were investigated. Culturing of myoblasts under these conditions led to an upregulation of almost all the investigated genes compared to normal nutrition. Under normal conditions, there was no positive effect of RSV on mitochondrial respiration in patients and controls. However, under restricted conditions, the respiratory factors measured by Seahorse were improved in the presence of RSV. Further studies are necessary to clarify the involved mechanisms and elucidate the controversial effects of resveratrol on SIRT1 and SIRT3 expression.